Quantitative measurement of interaction strength between kaolinite and different oil fractions via atomic force microscopy: Implications for clay-controlled oil mobility. (November 2021) - Liu, Yuke; Zhang, Shuichang; Zou, Caineng; Wang, Xiaomei; Sokolov, Igor; Su, Jin; Wang, Huajian; He, Kun
Abstract: Clay–oil interaction in unconventional shale reservoir plays a critical role in oil migration, which further governs the exploration of petroleum resource. In this study, interaction strength between kaolinite and different oil fractions (saturates, aromatics, resins and asphaltenes) were quantitatively investigated by atomic force microscopy (AFM). The AFM tips with various oil fraction coatings were monitored to approach and retract from kaolinite surface, from which the force curves with adhesion information were derived. As a result, kaolinite-oil interaction curves are characterized with large hysteresis, which is due to the adhesion behavior between two phases caused by a meniscus formed at contact area. Adhesive strength, including force and work, increases from nonpolar to polar organics in order of saturates, aromatics, resins and asphaltenes. The clay-oil interaction could be well depicted by using a combined force model composed of attractive van der Waals force, capillary force and intermolecular repulsive force. With the application of infrared spectroscopy in oil fractions, the difference of adhesion among various oil fractions was analyzed from a viewpoint of binding types between functional groups in oil and kaolinite. Compared with nonpolar saturates, it is the aromatic CC group in aromatics, and the carboxy (-COOH) functional group in polar resins and asphaltenes, that contributes to their strong adhesion with clay surface, respectively. Quantitatively, adhesion force and work caused by aromatic CC and –COOH are an order of magnitude higher than aliphatic CH2 +CH3 . These observations on interaction strength between kaolinite and different oil fractions, especially from a view of chemistry, yield much information on the mechanism of clay-controlled oil mobility in shale from a new perspective. Highlights: Interaction strength between kaolinite and oil fractions were quantitatively investigated by atomic force microscopy. Adhesion between oil and clay was attributed to aromatic C=C and carboxyl for aromatics and resin+asphaltenes, repectively. The interaction was depicted by a combination of van der Waals force, capillary force and intermolecular repulsive force.